Advancing DNA Barcoding and Metabarcoding Applications for Plants Requires Systematic Analysis of Herbarium Collections—An Australian Perspective - Dormontt, Eleanor E.; van Dijk, Kor-jent; Bell, Karen L.; Biffin, Ed; Breed, Martin F.; Byrne, Margaret; Caddy-Retalic, Stefan; Encinas-Viso, Francisco; Nevill, Paul G.; Shapcott, Alison; Young, Jennifer M.; Waycott, Michelle; et al. (Frontiers in Ecology and Evolution, 2018)
Building DNA barcode databases for plants has historically been ad hoc, and often with a relatively narrow taxonomic focus. To realise the full potential of DNA barcoding for plants, and particularly its application to metabarcoding for mixed-species environmental samples, systematic sequencing of reference collections is required using an augmented set of DNA barcode loci, applied according to agreed data generation and analysis standards. The largest and most complete reference collections of plants are held in herbaria. Australia has a globally significant flora that is well sampled and expertly curated by its herbaria, coordinated through the Council of Heads of Australasian Herbaria. There exists a tremendous opportunity to provide a comprehensive and taxonomically robust reference database for plant DNA barcoding applications by undertaking coordinated and systematic sequencing of the entire flora of Australia utilising existing herbarium material. In this paper, we review the development of DNA barcoding and metabarcoding and consider the requirements for a robust and comprehensive system. We analysed the current availability of DNA barcode reference data for Australian plants, recommend priority taxa for database inclusion and highlight future applications of a comprehensive metabarcoding system. We urge that large-scale and coordinated analysis of herbarium collections be undertaken to realise the promise of DNA barcoding and metabarcoding, and propose that the generation and curation of reference data should become a national investment priority.